Yield response and economic implications of soybean (Glycine max (L.). Merrill) – lowland-upland rice sequential cropping in the rainforest/savanna transitory ecosystem - Paul Abayomi Sobowale SOREMI; Olalekan Sulaimon SAKARIYAWO; Kehinde Adebayo OKELEYE; Victor Idowu O. OLOWE; Jamiu Oladipupo AZEEZ; Francis NWILENE; Sunday Gbenga ADERIBIGBE (Acta Agriculturae Slovenica)
A sequential cropping system of soybean-lowland (NERICA L-42)-upland (NERICA 2) rice was established at Abeokuta and Ibadan (Nigeria) to evaluate the performance of the cropping system. Field trials were in split-split plot arrangement fitted into randomised complete block design and replicated three times. The first sequence had in the main plot tillage [minimum (MT) and conventional (CT)]. Soybean varieties TGx 1448-2E (V1) and TGx 1740-2F (V2) in sub-plot and spacing in sub-sub plot were 60 cm × 5 cm (R1), 60 cm × 10 (R2) and 60 cm × 15 cm (R3). Individual rice plots were established by dry dibble (DD) seeding and transplanting and sub-sub plot spacing were 15 cm × 15 cm (S1), 20 cm × 20 and 25 cm (S2) × 25 cm (S3). The sequence soybean (V1 CT R3); lowland and upland rice (S3 CT DD) was the most economically efficient (N 1,754 ha-1 day-1) in Abeokuta, while soybean (V1 MT R1) and lowland and upland rice (S1 DD MT) was the most economically efficient (N 1,858 ha-1 day-1) in Ibadan.